2022
DOI: 10.3390/nu14051052
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Doses of Nitrate-Rich Beetroot Juice Do Not Modify Cognitive Function and Cerebral Blood Flow in Overweight and Obese Older Adults: A 13-Week Pilot Randomised Clinical Trial

Abstract: Nitrate-rich food increases nitric oxide (NO) production and may have beneficial effects on vascular, metabolic, and brain function. This pilot study tested the effects of prolonged consumption of a range of doses of dietary nitrate (NO3−), provided as beetroot juice, on cognitive function and cerebral blood flow (CBF) in overweight and obese older participants. The study had a 13-week single-blind, randomised, parallel design, and 62 overweight and obese older participants (aged 60 to 75 years) received the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…The review also highlighted the limitations of the studies (small sample size, short duration and use of healthy populations), which could have contributed to the limited efficacy of the dietary nitrate interventions. Since the publication of the review, additional studies (50,51,52,53,54,55,56) have been published on the topic; we have summarised in Fig. 2 a selection of studies that have investigated the effects of dietary nitrate on neurocognition and CBF following supplementation for at least 1 week and conducted in subjects at greater risk of cognitive impairment.…”
Section: Dietary Nitrate and Brain Healthmentioning
confidence: 99%
See 4 more Smart Citations
“…The review also highlighted the limitations of the studies (small sample size, short duration and use of healthy populations), which could have contributed to the limited efficacy of the dietary nitrate interventions. Since the publication of the review, additional studies (50,51,52,53,54,55,56) have been published on the topic; we have summarised in Fig. 2 a selection of studies that have investigated the effects of dietary nitrate on neurocognition and CBF following supplementation for at least 1 week and conducted in subjects at greater risk of cognitive impairment.…”
Section: Dietary Nitrate and Brain Healthmentioning
confidence: 99%
“…2 a selection of studies that have investigated the effects of dietary nitrate on neurocognition and CBF following supplementation for at least 1 week and conducted in subjects at greater risk of cognitive impairment. Only two studies have concomitantly measured both neurocognition, CBF or brain metabolites (50,51) , which was measured by magnetic resonance spectroscopy (51) and near-infrared spectroscopy (50) . Five studies (50,51,53,55,56) assessed changes in cognitive function, and three (51,55,56) reported significant changes in executive function, vigilance and motor skills.…”
Section: Dietary Nitrate and Brain Healthmentioning
confidence: 99%
See 3 more Smart Citations